1995
DOI: 10.1080/00420989550012609
|View full text |Cite
|
Sign up to set email alerts
|

Entry in Greek Manufacturing Industry: Athens vs the Rest of Greece

Abstract: Sum m ary. T he paper reports an attem pt to estim ate the deter minants of entry in G reek m anufacturing industry in the 1984± 87 perio d and to identify the differe nces betw een locatio nal entry prefere nces. E ntry in Athens is found to be hesita nt with respect to factor s such as pro® tability and increase d competitio n. Conversely , entry in the rest of the country is strongly relate d to expected pro® ts and safe m arkets, negativel y affecte d by relativ e labour costs and indiffere nt to internati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
2

Year Published

1999
1999
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 20 publications
2
9
0
2
Order By: Relevance
“…Miller (1992) also suggests that hybrid strategies are perhaps most appropriate in an era of hypercompetition, which now prevails in many industries, because it not only reduces the perils of specialization but also allows firms to profit from multiple abilities and exploits potential synergies among the different strategy aspects. Some research has also shown that a balanced strategic position may be more appropriate for firms operating in mature industries with standardized products (Hall, 1980; Louri and Anagnostaki, 1995). Therefore, the possibility of a firm pursuing both generic strategies simultaneously cannot be precluded.…”
Section: Literature Review and Hypothesessupporting
confidence: 78%
“…Miller (1992) also suggests that hybrid strategies are perhaps most appropriate in an era of hypercompetition, which now prevails in many industries, because it not only reduces the perils of specialization but also allows firms to profit from multiple abilities and exploits potential synergies among the different strategy aspects. Some research has also shown that a balanced strategic position may be more appropriate for firms operating in mature industries with standardized products (Hall, 1980; Louri and Anagnostaki, 1995). Therefore, the possibility of a firm pursuing both generic strategies simultaneously cannot be precluded.…”
Section: Literature Review and Hypothesessupporting
confidence: 78%
“…An attempt to evaluate the effect of sectoral policy in manufacturing entry (1982)(1983)(1984)(1985)(1986)(1987)(1988) was then made , focusing on features of already built-up firms as explanatory variables. Finally, closer in perception to the present paper are Louri and Anagnostaki (1995) who examine entry decisions in Greek manufacture in the 1984-1987 period, providing useful hints on differences between…”
Section: Introduction and Related Literaturementioning
confidence: 77%
“…Analysis reveals that agglomeration economies in the form of localization economies play a significant role in all cases except tourism, while other controlling factors are also present. In particular, the positive effects of urbanization economies (Carod & Antolin 2004;Campi et al 2004;Louri 1988;Louri & Anagnostaki 1994) have not been verified here. The effect of Marshallian type and of Jacobian type localization economies (Feldman & Audretsch 1999;Duranton & Puga 2000;Campi et al 2004;Carod & Antolin 2004;Frenken et al 2007) have been confirmed in the present study, suggesting that these are important factors for the location of start-ups in Greece.…”
Section: Discussionmentioning
confidence: 62%
“…Existing empirical research regarding the formation of regional location patterns in Greece is limited. Louri (1988) and Louri and Anagnostaki (1994) suggest that urbanization economies largely explain the location of manufacturing industries in urban centres. Fotopoulos and Spence (1998;1999) suggest that agglomeration economies determine the spatial variation of new firm location in Greece, while Fotopoulos and Louri (2000) find that the survival rates of firms increase through successful location choices.…”
Section: Introductionmentioning
confidence: 99%